The health of postnatal women's partners up to 18 months after their baby was born: a longitudinal survey alongside a randomised controlled trial. (13th September 2011) - Morrell, CJ; Slade, P; Walters, SJ
Abstract : Background: Women's depression may affect partners who may also become depressed thereby reducing their ability to support the mother and care for the new infant, or other children. Compared with depressive symptoms among women, little is known about depression in postnatal men or example how their health status changes over time. Depression may not be recognised because of men's reluctance to disclose personal feelings or their less frequent contact with healthcare professionals. Aim: To examine the self-perceived health status, by postal questionnaire, in women's partners at 6, 12 and 18 months after their baby was born, comparing the health of those men whose partner was at greater risk of postnatal depression, indicated by a 6-week baseline Edinburgh Postnatal Depression Scale (EPDS) score ≥12, with those at less risk. Methods: 4084 women consented to take part in a cluster randomised controlled trial (RCT) and economic evaluation of training for health visitors to support postnatal women; the main trial outcomes are published. When the women were followed-up by postal questionnaire, a separate questionnaire was included for their partners to complete at the same 6, 12 and 18 month time points. These questionnaires included demographic questions, the Short Form-36 (SF-36) (for Mental Component Summary (MCS) and Physical Component Summary (PCS)), Measure of Social Relationships, Life Events Questionnaire, Parenting Stress Index Short-Form and Dyadic Adjustment Scale Short-Form; and theClinical Outcomes in Routine Evaluation Outcome Measure (CORE-OM) at 18 months. Results: 2875 women and 2201 of their partners returned a 6-month postnatal questionnaire. The men's mean age was 33.9 years (SD 5.8); most (96.3%, 2076/2201) were white; for most, English was first language (97.5%, 2114/2201). There were statistically significant differences between the mean scores for partners of women with an EPDS score ≥12 and those whose EPDS scores were <12, in MCS and SF-6D at 6, 12 and 18 months postnatally; in PCS at 6 and 12 months postnatally and in CORE-OM scores at 18 months postnatally, with scores indicating poorer health among the partners of women with an EPDS score ≥12. The mean difference in MCS at 6 months, was 3.7 (95% CI 2.6 to 4.8, p=0.001) and in SF-6D at 6 months, was 0.06 (95% CI 0.04 to 0.07, p=0.001). Conclusions/recommendations: These findings indicate that in addition to assessing the mental health of postnatal women, attention should be paid to the potential impact on the mental health of postnatal men. More research should be undertaken to explore whether depression in one partner might help explain depression in the other partner.